The glass hotel - Mandel, Emily St. John, 1979- (Alfred A. Knopf, 2020)
"From the award-winning author of Station Eleven, a captivating novel of money, beauty, white-collar crime, ghosts, and moral compromise in which a woman disappears from a container ship off the coast of Mauritania and a massive Ponzi scheme implodes in New York, dragging countless fortunes with it"--